Shape memory polymers in osteochondral tissue engineering - Sepideh Saghati; Reza Rahbarghazi; Sonia Fathi Karkan; Sajed Nazifkerdar; Ali Baradar Khoshfetrat; Hamid Tayefi Nasrabadi (Journal of Research in Clinical Medicine, 2022)
Bone and cartilage injuries are significantly increasing with population aging. Tissue engineering is considered an alternative and promising approach for alleviating osteochondral tissue injuries along with available therapeutic modalities. 3D- and 4D-printing fabrication protocols have been used to facilitate the production of bone/cartilage scaffolds that are similar to bone and cartilage microenvironments. In this regard, advanced biomaterials, including smart polymers and stimuli-responsive polymers are the first essential elements for improved bone/cartilage regeneration. Shape-memory polymers, are stimuli-responsive materials and are available in permanent and temporary structures. The application of shape-memory scaffolds can lead to providing in vivo-like conditions and improve cell bioactivity and phenotype acquisition. In this review article, we tried to highlight stimuli-responsive polymers and their application in osteochondral tissue engineering.